Relação entre cefaleia e o uso de equipamentos de proteção individual em cirurgiões-dentistas e médicos do Rio Grande do Norte durante a COVID-19 - Bertoldo, Mariana Rios (2021)
Introduction: The alertness caused by the disease of the new Coronavirus (COVID-19) can have a negative impact on the health of individuals. Health professionals are exposed to the contamination by the virus, especially the Dental Surgeons and Doctors, who work in a hospital environment, due to their frequent action close to the patient. It is known that headache may be related to individual protective equipment (EPIS) used in the daily lives of these professionals. Objective: The present study seeks to evaluate the association of headache and the use of personal protective equipment in Dental Surgeons and Doctors in Rio Grande do Norte. Methodology: An observational, analytical and cross-sectional study was carried out with dental surgeons and doctors invited to participate in the survey via electronic messages through Google forms about signs and symptoms, through the questionnaire for headache (Questionnaire of headaches associated with equipment personal protection - Adapted). For statistical analysis the data were gathered in a database created in the program Statistical Package for the Social Science (SPSS) 22.0. Pearson and Fischer Chi-square tests were performed to cross the variables, with a 95% confidence interval. Results: The study sample consisted of 181 professionals, being 23.2% doctors (n = 42) and 76.8% dentists (n = 139), 34.8% (n = 63) male and 65 , 2% (n = 118) of the female gender. 84% (n = 152) of the professionals worked in an outpatient setting. 43.6% of professionals (n = 79) reported a positive response to headache. An increase in the use of EPIS (87.3% n = 158) (p = 0.183), use of facial masks with glasses or visors (96.7% n = 175), (p = 0.234) or N95 or PFF- masks 2 (88.4% n = 160) (p = 0.062) were not related to headache. However, its use for 5 hours or more (58.6% n = 106) (p <0.01) was statistically significant. Reports of bilateral headache, pain in the parietal and temporal region and throughout the head, quality of pain, time interval and intensity, were significant for the development of headache due to the use of PPE. Conclusions: Based on our study, the increased use of PPE did not statistically influence headache. It was observed that the type of mask used did not influence the headache reports and there was an increase in headache reports in those professionals who used them for about five hours or more.